Regular moderate aerobic exercise improves high-fat diet-induced nonalcoholic fatty liver disease via monoacylglycerol O-acyltransferase 1 pathway suppression - Kyung-Wan Baek; Jeong-An Gim; Jung-Jun Park (Journal of Sport and Health Science, 2020)
Purpose: Monoacylglycerol O-acyltransferase 1 (MGAT1) is reported to play a key role in the development of diet-induced nonalcoholic fatty liver disease (NAFLD). Thus, this study investigated the effect of exercise on suppression of the MGAT1 pathway in NAFLD tissue of high-fat diet (HFD)-induced obese rats. Methods: Male Sprague-Dawley rats were fed an HFD containing 45% fat for 6 weeks. Upon confirmation that NAFLD had been induced in the obese animals, they were divided into HFD-fed groups provided with exercise (HFD + EXE) or without exercise (HFD) and a group given dietary adjustment (DA) only, for a further 6 weeks of intervention treatment. The 6-week regular moderate aerobic exercise consisted of an accommodation phase with increasing exercise. Lipid accumulation in the liver tissue was determined by Oil Red O staining. The MGAT1 and liver lipogenic gene mRNA levels were measured by qPCR, and their protein levels by western blot assay. Results: Oil Red O staining showed that NAFLD was successfully induced by HFD-fed. The gene expression of MGAT1 was significantly lower in HFD + EXE than HFD. However, there was no significant difference between HFD + EXE and DA. The protein expression of MGAT1 was significantly lower in HFD + EXE than both HFD and DA. Messenger RNA and protein expression of other lipogenic genes were not different among groups. These data indicate that exercise suppresses MGAT1 pathway regardless of HFD feeding; in part, this effect could be greater than DA. Conclusion: Our data suggest that exercise can improve NAFLD, which is probably due to suppression of MGAT1 pathway.